Low-Cost Sensors and Biological Signals - Dierick, Frédéric; Buisseret, Fabien; Eggermont, Stéphanie (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Many sensors are currently available at prices lower than USD 100 and cover a wide range of biological signals: motion, muscle activity, heart rate, etc. Such low-cost sensors have metrological features allowing them to be used in everyday life and clinical applications, where gold-standard material is both too expensive and time-consuming to be used. The selected papers present current applications of low-cost sensors in domains such as physiotherapy, rehabilitation, and affective technologies. The results cover various aspects of low-cost sensor technology from hardware design to software optimization.